NEED ANALYSIS ON DEVELOPING SKILL-BASED MATERIALS FOR D3 NURSING STUDENTS - Yansyah Yansyah; Dina Rafidiyah; Hafizhatu Nadia (English Department of Faculty of Tarbiyah and Teacher Training, 2019)
The present study aims to help nursing students to prepare the language skills required in the workplace. Need analysis was conducted to map the students’ need so suitable materials can be designed for effective teaching. There were fifteen students of D3 Nursing in the University of Muhammadiyah Banjarmasin invited to be the participants of this research. The data were gathered by conducting a depth interview with the English lecturer, BP3TKI South Kalimantan, alumni who worked abroad, and the head of D3 nursing department. It was intended to collect data related to important language skills the students need to master. Besides, a questionnaire was also employed to get data regarding the students’ need, want, and lack. The findings showed that D3 nursing students need to master at least three skills, such as basic English, work-related language skills, and academic-related language skills to enable them to go International.